Propuesta Del Programa De Gobierno De Datos Para La Organización Agencias Sas (2023)
In a business environment significantly influenced by the power of data, Agencias SAS finds itself in a critical situation. Despite managing a vast amount of information, it faces a substantial challenge in terms of data asset efficiency and structuring. These hampers informed decision-making and can have an adverse impact on its operational processes and competitiveness.